[How] Do Users Benefit From Giving Consent? - Pandit, Harshvardhan (My University, 2021)
Consent is meant to empower users by giving them a choice regarding the use of their personal data. Thus, organisations have the incentive to provide benefits, whether directly or indirectly, in return for consent. However, recent research has demonstrated the scale and scope of malpractices regarding consent on the web, where users are misled and coerced into giving away their personal data and privacy. In light of this, we call for investigating what benefits, if any, are specified in the context of consent; who benefits from it; and whether they can be observed in reality. We hope our work outlines the need to formally investigate the claims made when requesting consent and empowers users through greater transparency regarding benefits to make better-informed choices.
5th Workshop on Technology and Consumer Protection (ConPro) - co-located with IEEE Symposium on Security and Privacy (IEEE S&P)
PRESENTED
Virtual / Online
Keywords: Privacy; Consent; Dark patterns; Empowerment; Transparency; Human-centricity; Evaluation methodology